Changing Teacher Education: Challenging Assumptions and Moving Forward - Todd Goodson (Educational Considerations, 2018)
This issue marks the first under the direction of the Department of Curriculum and Instruction at Kansas State University. This issue is devoted to the theme Changing Teacher Education, and our contributing authors explore various aspects of change and their implications for both teacher education as well as K-12 education. The issue also includes a new feature, Key Conversations, devoted to an interview with a leading figure whose work illuminates the theme of the issue.
Keywords: Lead Editorial